2
$\begingroup$

Solve $(1+x)y’=y$ by power series. $$$$Start with $y$ and $y’$:

$y=a_0+a_1x+a_2x^2+a_3x^3+...+a_nx^n$

$y’=a_1+2a_2x+3a_3x^2+...+na_nx^{n-1}$

Then $(1+x)y’=a_1(1+x)+2a_2(1+x)x+3a_3(1+x)x^2+...+na_n(1+x)x^{n-1}$

Then $(1+x)y’-y=[a_1(1+x)+2a_2(1+x)x+3a_3(1+x)x^2+...+na_n(1+x)x^{n-1}]-[a_0+a_1x+a_2x^2+a_3x^3+...+a_nx^n]=0$ $$$$$\implies [a_1+a_1x+2a_2x+2a_2x^2+3a_3x^2+3a_3x^3+...+(na_n+na_nx^n)]-[a_0+a_1x+a_2x^2+a_3x^3+...+a_nx^n]=0$$$$$$(a_1-a_0)+(a_1+2a+2-a_1)x+(2a_2+3a_3-a_2)x^2+(3a_3+a_3)x^3+...+=0$

I’m missing the trick when equating terms. Any help would be appreciated!

$\endgroup$
  • $\begingroup$ All x coefficents should be zero since you want it for $\forall x$ note that we use infinite series normally $\endgroup$ – Isham Apr 9 '18 at 18:27
1
$\begingroup$

Let $y(x) = \sum_{i=0}^\infty y_i x^i$. Then $y'(x) = \sum_{i=0}^\infty i y_i x^{i-1} = \sum_{j=0}^\infty (j+1) y_{j+1} x^{j}$ where we get this by substituting $i=j+1$ and noting that when $i=0$ the term is $0$ so we don't get in trouble concerning $y_{-1}$.

Then $x y'(x) = \sum_{i=0}^\infty (i+1) y_{i+1} x^{i+1} = \sum_{j=1}^\infty j y_{j} x^{j} = \sum_{j=0}^\infty j y_{j} x^{j} - y_0 x^0$

and our equation becomes (using the notation that $[j=0]$ means $1$ if $j$ is $0$ and $0$ otherwise)

$$ \sum_{j=0}^\infty (j+1) y_{j+1} x^{j} + \sum_{j=0}^\infty j y_{j} x^{j} -[j=0]y_0 = \sum_{j=1}^\infty y_j x^j $$

Now the trick of the power series method: You can set the coefficients of each $x^j$ to match, for each individual $j$. Thus:

$$ \forall j : (j+1)y_{j+1} + jy_j -[j=0]y_0 = y_j \\ y_{j+1} = \left(-\frac{j-1- [j=0]}{j+1} \right) y_j \\y_1 = -\frac{0-1-1}{1}y_0 = y_0 \\y_2 = -\frac{1-1-0}{2}y_1 = 0 \\y_3 = -\frac{2-1-0}{3}y_2 = -\frac23 y_2 = 0 \\ \forall j\geq 2 : y_j = 0 $$ So the general form of solution is $$ y = y_0 + y_0 x = y_0 (1+x) $$

Note that because of the pleasant termination once $y_2 = 0$, this method produces an exact answer for this equation. Also note that our excursion through the "land of log" has been eliminated.

$\endgroup$
3
$\begingroup$

Are you required to "use series"? Here's a very quick solution. Rewrite it as $$ \frac{y'}{y} = \frac{1}{1+x}. $$ Note that $$ \frac{y'}{y} = \frac{d\phantom{x}}{dx}\ln(y) $$ and $$ \frac{1}{1+x} = \frac{d\phantom{x}}{dx}\ln(1+x). $$ Integrating gives $$ \ln(y) = \ln(1+x) + C. $$ Therefore $y=c(1+x)$.

$\endgroup$
2
$\begingroup$

Hint

1) By power serie means infinite series $$y=\sum_{n=0}^{\infty}a_nx^n$$ note that : $$y'=\sum_{n=0}^{\infty}a_nnx^{n-1}=\sum_{n=1}^{\infty}a_nnx^{n-1}=\sum_{n=0}^{\infty}a_{n+1}(n+1)x^{n}$$

2) Try to use the sigma notation it's easier $$(1+x)y’=y$$ Becomes $$(1+x)\sum_{n=0}^{\infty}a_{n+1}(n+1)x^{n}=\sum_{n=0}^{\infty}a_nx^{n}$$ $$......$$ 3) All the coefficents should be zero since we want the equality to hold $\forall \, x$ $$\sum_{n=0}^{\infty}a_nx^{n}=0 \implies a_n=0 \,\, n=1,2,3.....$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.